Colorimetric Detection of Salicylic Acid in Aspirin Using MIL-53(Fe) Nanozyme - Liang, Ling; Huang, Yaojing; Liu, Wenren; Zuo, Weiyuan; Ye, Fanggui; Zhao, Shulin (Frontiers in Chemistry, 2020)
The impurity salicylic acid (SA) in aspirin is a required inspection item for drug quality control. Since free SA has a significant toxic for human, hence, the content determination of free SA is absolutely necessary to ensure people’s health. In this work, a facile colorimetric method was developed for the detection of SA in aspirin by utilizing MIL-53(Fe) nanozyme. As MIL-53(Fe) possesses enzyme mimics catalytic activity, 3,3,5,5-tetramethylbenzidine (TMB) can be easily oxidized to blue oxidized TMB (oxTMB) with the existence of H2O2. Moreover, an inhibition effect on the catalytic activity of MIL-53(Fe) nanozyme is induced due to the specific complexation between SA and Fe3+ in the centre of MIL-53(Fe), which results in a lighter color in the oxTMB. The color change of oxTMB can be easily recognized by naked eye with the addition of different concentrations of SA. Thus, a simple colorimetric platform was established effectively for monitoring SA. A good linear relationship (R2=0.9990) was obtained in the concentration range of 0.4-28 μmol L-1, and the detection limit was 0.26 μmol L-1. In particular, the rationally designed system has been well applied to the detection of SA impurity in aspirin. Satisfyingly, the detection results are highly in accord with those of HPLC. This novel colorimetric platform broadens the application prospects of nanozymes in the field of pharmaceutical analysis.